Urbanization and Health Conditions in Nigeria: Dealing with the Urban Health Challenges - Ubong Edem Effiong; Supper Roland Okijie; Muhammad Ridwan (Budapest International Research and Critics University, 2021)
Health concerns arising from urbanization requires serious commitment to revamp the Nigerian health sector. In that regards, this study sought to investigate the influence of urbanization and health expenditure on life expectancy and mortality rates in Nigeria from 1981 to 2020. The fully modified ordinary least squares (FMOLS) technique was used to ascertain the influence of urbanization and government health expenditure on life expectancy and mortality rates in Nigeria. From the result of FMOLS, it was observed that urbanization exerts a positive and significant effect on life expectancy; but exerts a negative and significant effect on mortality rates. Moreover, government health expenditure generated a negative and significant effect on life expectancy, but a positive and significant effect on adult mortality. As such, the 15% recommended by the World Health Organization should be given a top priority in order to alleviate the country out of the menace of health tourism that has bedevilled the country over the years.